Rapid progression of marginal zone B-cell lymphoma after COVID-19 vaccination (BNT162b2): A case report - Sekizawa, Akinori; Hashimoto, Kenichi; Kobayashi, Shinichi; Kozono, Sawako; Kobayashi, Takahiro; Kawamura, Yusuke; Kimata, Motohiro; Fujita, Naoya; Ono, Yosuke; Obuchi, Yasuhiro; Tanaka, Yuji (Frontiers in Medicine, 2022)
B-cell lymphomas are neoplastic diseases occasionally associated with chronic inflammation. mRNA vaccines for coronavirus disease 2019 (COVID-19) induce inflammatory responses, which often lead to fever and lymphadenopathies indistinguishable from lymphomas. Although both lymphadenopathies and lymphomas can be influential, the correlation between them is unclear. Herein, we present the first case of marginal zone B-cell lymphoma following mRNA COVID-19 vaccination. An 80-year-old Japanese woman presented with a right temporal mass that appeared the morning after she was administered her first mRNA COVID-19 vaccination (BNT162b2). The mass gradually decreased in size but persisted over 6 weeks after her first vaccination (3 weeks after her second vaccination). At her first visit to our hospital, ultrasound revealed the size of the mass to be 28.5 × 5.7 mm, and computed tomography revealed multiple lymphadenopathies in the right parotid, submandibular, jugular, and supraclavicular regions. Initially, we suspected head-and-neck benign lymphadenopathy as a side effect of vaccination. Nine weeks later, the number of swollen submandibular and parotid glands increased, and the lymph nodes further enlarged. Finally, the right temporal mass was diagnosed as marginal zone B-cell lymphoma based on immunohistochemical and flow cytometry findings of biopsy specimens. Our findings suggest that although 4–6 weeks of observation for lymph node inflammation after the second vaccination is recommended, malignancy should also be considered in the differential diagnosis of lymphadenopathy following vaccination.